Effects of high intensity pulsed electric fields on yield and chemical composition of rose essential oil - Yajun, Zhou; Changmei, Xue; Susu, Zhang; Guangming, Yao; Ling, Zhang; Shujie, Wang (International Journal of Agricultural and Biological Engineering, 2017)
Abstract: High intensity pulsed electric fields (PEF) combined with distillation was used to extract essential oil from rose. Three main parameters, namely electric field intensity, pulse number and distillation times, which can affect the efficiency of extraction, were optimized. Then, in order to demonstrate the feasibility of the method, oil obtained under optimal conditions was compared quantitatively and qualitatively with that obtained by conventional hydro distillation. Considering the extraction yield, the optimal parameters combination was obtained with electric field intensity of 20 kV/cm, pulse number of 8 and distillation time of 2 h. PEF treatment had no significant influence on the quality of essential oils. However, there was an increase in methyl eugenol percentage, which is a disadvantage from qualitative point of view. Keywords: rose, hydro distillation, pulsed electric fields, PEF, extraction, essential oil DOI: 10.3965/j.ijabe.20171003.3153 Citation: Zhou Y J, Xue C M, Zhang S S, Yao G M, Zhang L, Wang S J. Effects of high intensity pulsed electric fields on yield and chemical composition of rose essential oil. Int J Agric & Biol Eng, 2017; 10(3): 295–301.